Left ventricular function, congestion, and effect of empagliflozin on heart failure risk after myocardial infarction - Udell, Jacob A.; Petrie, Mark C.; Jones, W. Schuyler; Anker, Stefan D.; Harrington, Josephine; Mattheus, Michaela; Seide, Svenja; Amir, Offer; Bahit, M. Cecilia; Bauersachs, Johann; Bayes-Genis, Antoni; Chen, Yundai; et al. (Journal of the American College of Cardiology, 2024)
Background - Empagliflozin reduces the risk of heart failure (HF) hospitalizations but not all-cause mortality when started within 14 days of acute myocardial infarction (AMI). - Objectives - This study sought to evaluate the association of left ventricular ejection fraction (LVEF), congestion, or both, with outcomes and the impact of empagliflozin in reducing HF risk post-AMI. - Methods - In the EMPACT-MI (Trial to Evaluate the Effect of Empagliflozin on Hospitalization for Heart Failure and Mortality in Patients with Acute Myocardial Infarction) trial, patients were randomized within 14 days of an AMI complicated by either newly reduced LVEF<45%, congestion, or both, to empagliflozin (10 mg daily) or placebo and were followed up for a median of 17.9 months. - Results - Among 6,522 patients, the mean baseline LVEF was 41 ± 9%; 2,648 patients (40.6%) presented with LVEF <45% alone, 1,483 (22.7%) presented with congestion alone, and 2,181 (33.4%) presented with both. Among patients in the placebo arm of the trial, multivariable adjusted risk for each 10-point reduction in LVEF included all-cause death or HF hospitalization (HR: 1.49; 95% CI: 1.31-1.69; P < 0.0001), first HF hospitalization (HR: 1.64; 95% CI: 1.37-1.96; P < 0.0001), and total HF hospitalizations (rate ratio [RR]: 1.89; 95% CI: 1.51-2.36; P < 0.0001). The presence of congestion was also associated with a significantly higher risk for each of these outcomes (HR: 1.52, 1.94, and RR: 2.03, respectively). Empagliflozin reduced the risk for first (HR: 0.77; 95% CI: 0.60-0.98) and total (RR: 0.67; 95% CI: 0.50-0.89) HF hospitalizations, irrespective of LVEF or congestion, or both. The safety profile of empagliflozin was consistent across baseline LVEF and irrespective of congestion status. - Conclusions - In patients with AMI, the severity of left ventricular dysfunction and the presence of congestion was associated with worse outcomes. Empagliflozin reduced first and total HF hospitalizations across the range of LVEF with and without congestion. (Trial to Evaluate the Effect of Empagliflozin on Hospitalization for Heart Failure and Mortality in Patients with Acute Myocardial Infarction [EMPACT-MI]; NCT04509674)